IoT-Based Monitoring System To Support Village Food Security In The Smart Village Concept - Nunsina Nunsina; Zahratul Fitri; Nazimah Nazimah; Ananda Faridhatul Ulva (Brilliance: Research of Artificial Intelligence, 2025)
Food security is a critical issue that directly affects a nation’s social, economic, and political stability. The growing demand for staple foods such as rice, corn, and soybeans continues to exceed domestic production capacity, posing challenges to sustainable agricultural development. To overcome these issues, the Smart Village concept presents an innovative solution by integrating digital technology into rural agricultural systems. This study focuses on applying the Internet of Things (IoT) to enhance agricultural productivity and food security in Bireuen Regency. An IoT-based monitoring prototype was developed to regulate essential environmental parameters—pH, electrical conductivity (EC), nutrient solution temperature, and air humidity—through real-time sensor data collection and automated control. Experimental implementation revealed that the system effectively maintained optimal conditions: pH between 5.5–6.5, EC from 1.2–2.0 mS/cm, temperature between 20–28 °C, and humidity ranging from 65–80%. These controlled conditions created a stable growing environment that significantly improved crop performance. The results demonstrated measurable benefits: lettuce productivity increased by 18%, water-use efficiency improved by 27%, and crop failure rates decreased by 20%. Such improvements indicate that IoT technology not only stabilizes environmental variables but also enhances resource utilization and supports sustainable farming practices. Overall, the integration of IoT-based monitoring systems within the Smart Village framework represents a strategic approach to modern agriculture, promoting efficiency, sustainability, and rural independence in food production.